Development of thermally stable and hygienic colored cotton fabric made by treatment with natural coconut shell extract. (July 2018) - Teli, MD; Pandit, Pintu
As far as the value addition of textile is concerned, flame retardancy of textile materials is considered to be one of the most important properties in textile finishing by both industries as well as academic researchers. Flame-retardant property with thermal stability was imparted to cotton by using green coconut ( Cocos nucifera Linn) shell extract, a natural waste source of coconut. Coconut shell extract was analyzed by high-performance liquid chromatography, Fourier transform infrared spectroscopy, energy-dispersive spectrometry and its phytochemical analysis was also carried out. The coconut shell extract (acidic after extraction) was applied in three different pH (acidic, neutral, and alkaline) conditions to the cotton fabric. Flame-retardant properties of the untreated and the treated cotton fabrics were analyzed by limiting oxygen index and vertical flammability. The study showed that all the treated fabrics had good flame resistance property compared to that of the untreated fabric. The limiting oxygen index value was found to increase by 72.2% after application of the coconut shell extract from alkaline pH. Pyrolysis and char formation behavior of the concerned fabrics were studied using thermogravimetric analysis and differential scanning calorimetric analysis in a nitrogen atmosphere. The physicochemical composition of the untreated and coconut shell extract treated cotton fabrics were analyzed by attenuated total reflection–Fourier transform infrared, scanning electron microscope, and energy-dispersive X-ray spectroscopy. Also, treated cotton fabric showed natural brown color and antibacterial property against both Gram-positive and Gram-negative bacteria. The durability of the flame-retardant functionality to washing with soap solution has also been studied and reported in this paper.